Avaliação da satisfação dos usuários de um ambulatório hospitalar integrante do Sistema Único de Saúde - Aguiar, Antonio Célio de (2009)
The present research had the objective of evaluate the satisfaction degree of the users of an hospital ambulatory clinic that attends, between others, to the functionaries of the Federal University of the Ceará The sector named of Servant’s Ambulatory it is located in the dependences of the Walter Cantídio Academic Hospital and the clients are attended through the Unique System of Health. The study had a predominantly qualitative approach despite of to have utilized also the quantitative approach for that the objectives proposed went achieved. To research worked with a sample of 158 functionaries users of the ambulatory clinic that answered questions about date social demographic. Also it was deed a cutting in the sample of random way for that went applied an interview whose answers served of subsidy in the formulation of the final result of the research. For the application of the interview did not itself size up previously the number of researched that should answer her. It utilized itself the beginning of the saturation. air the application of the interview did not itself size up previously the number of researched that should answer her. It utilized itself the beginning of the saturation. Considering that the programs of attention in health need process of evaluation that enable the reflection of the points it will be overhauled and that the evaluation of the satisfaction of the user represents a form of adapt the service, the present study enabled the knowledge of a reality that happens in the Servant`s Ambulatory. The results aimed for the verification of that the majority of the users is satisfied with the service, detaching, but some claims made that, if attended, will contribute for a better service or for the reduction of the problems of the sector studied, aimed by them researched.